Suicide risk and mental health in the general population of French Polynesia. Issue 10 (October 2022) - Amadéo, Stéphane; Benradia, Imane; Sy, Aminata; Rereao, Moerani; Favro, Patrick; David-Vanquin, Germaine; Meunier-Tuheaiva, Annie; Lacoste, Jérôme; Fenni, Alban; Nguyen, Ngoc Lam; Goodfellow, Benjamin; Jehel, Louis; et al.
Objective: There are no reports on the burden of suicidal ideation and suicide attempts in the general population of French Polynesia (FP). We aimed to improve suicide prevention and mental health care by assessing the prevalence of suicide risk and major mental health disorders and care among adults in FP. Methods: We conducted the Mental Health in General Population Survey in FP during 2015 to 2017. Participants were selected using the quota method to obtain a representative sample of the general population. Suicide risk and psychiatric diagnoses were assessed using the Mini International Neuropsychiatric Interview. Results: We included 968 people aged 18 years or older. The prevalence of current suicidal ideation (13.1%) and current (2.6%) and lifetime suicide attempts (18.6%), as well as mental health disorders (42.8%), was high in FP. A notable proportion of participants with these conditions did not seek medical assistance. Conclusion: A high prevalence of suicide risk and mental health disorders was found in the general population of FP. Suicide prevention and mental health plans are needed in FP that include better access to primary care for the diagnosis and treatment of mental health disorders. Further research is needed to clarify cultural risk and protective factors.